Names of authorial bakings in Polish culinary shows - Burska, Katarzyna (Papers in Linguistics, 2021)
The names of the dishes play an important role, because they often determine the choice of the consumer in a restaurant or shop or encourage them to cook them themselves. The aim of the article is a semantic and pragmatic analysis of the names of bakings in the Polish cooking show „Bake off – Ale ciacho!” broadcast on TVP2 in the years 2016–2019. The research material consists of 300 examples. Almost an obligatory element of each analyzed name is the name of the participant, which has an informative function. In many names, the marketing function is emphasized. They not only provide information about ingredients, origin of products, baking properties, its purpose or method of baking, but also are designed to stimulate the senses, impose positive valuation, often using rich metaphors.